Growth and Survival Rate of Striped Eel Catfish Fingerlings (Plotosus lineatus) at Different Sizes: Growth and Survival Rate of Striped Eel Catfish Fingerlings - Asriyana Asriyana; Halili Halili; Abdul Muis Balubi; Asnawati Asrari; Raudhatul Mahdaniah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Striped eel catfish (Plotosus lineatus) are fish that live in coastal waters but there are also those that live in river mouths. This study aimed to determine the growth and survival rate of striped eel catfish fingerlings at different sizes in controlled media. This study used a completely randomized design (CRD) with three treatments (different sizes) and three replications, so there were nine experimental containers. The treatments used were treatment A: maintenance of fingerlings size (3.5-4.0 cm); treatment B: maintenance of fingerlings size (4.9-5.6 cm); and treatment C: maintenance of fingerlings size (7.0-8.0). During maintenance, absolute length gain, relative growth rate, specific growth rate, and fingerlings survival were determined. The results showed that fingerling size had a significant effect on growth performance and survival. Fingerlings measuring 4.9-5.6 cm had the highest growth performance, while fingerlings measuring 7.0-8.0 cm showed the highest survival rate than other sizes. This indicates that the fingerlings measuring 4.9-5.6 cm and 7.0-8.0 cm are suitable for aquaculture.